Leadership Experiences, Labor Market Entry, and Early Career Trajectories - Martin Lundin; Oskar Nordström Skans; Pär Zetterberg (Institute of Labor Economics (IZA), 2018)
Matching archive data on election discontinuities to register data on labor market trajectories we estimate the causal effects of being elected into Swedish student union councils on subsequent labor market careers. Marginally elected students are much more likely to have a rapid transition into employment. Effects are not confined to establishments, organizations or industries where previous candidates are employed, suggesting that the benefits are general in nature. Elected representatives have higher labor earnings within three years, but not thereafter. Overall, leadership experiences before labor market entry boost individuals' early careers, whereas mid-term outcomes are unaffected.
Keywords: I26; I23; J24; 330; extracurricular activities; earnings; higher education